Functional Dissociation of the Posterior and Anterior Insula in Moral Disgust - Ying, Xiaoping; Luo, Jing; Chiu, Chi-yue; Wu, Yanhong; Xu, Yan; Fan, Jin (Frontiers in Psychology, 2018)
The insula is thought to be involved in disgust. However, the roles of the posterior insula (PI) and anterior insula (AI) in moral disgust have not been clearly dissociated in previous studies. In this functional magnetic resonance imaging study, the participants evaluated the degree of disgust using sentences related to mild moral violations with different types of behavioral agents (mother and stranger). The activation of the PI in response to the stranger agent was significantly higher than that in response to the mother agent. In contrast, the activation of the AI in response to the mother agent was significantly higher than that in response to the stranger agent. These data suggest a clear functional dissociation between the PI and AI in which the PI is more involved in the primary level of moral disgust than is the AI, and the AI is more involved in the secondary level of moral disgust than is the PI. Our results provide key evidence for understanding the principle of embodied cognition and particularly demonstrate that high-level moral disgust is built on more basic disgust via a mental construction approach through a process of embodied schemata.